2021
DOI: 10.1021/acsomega.1c00583
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Humic Acid/l-Cysteine-Codecorated Magnetic Fe3O4 Nanoparticles for Selective and Highly Efficient Adsorption of Mercury

Abstract: Humic acid and L-cysteine-codecorated magnetic Fe 3 O 4 nanoparticles (HA/LC-MNPs) were synthesized using a coprecipitation method. Humic acid fractions abundant with carboxyl and hydroxyl groups can be selectively coated on the surface of MNPs during synthesis. HA/LC-MNPs with abundant heteroatoms (N, S, and O) show excellent removal capacity, great selectivity, and also fast trapping of Hg 2+ in a wide pH range. The adsorption capacity of HA/LC-MNPs for Hg 2+ can reach 206.5 mg/g, and the chemisorption was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The N(1s)-core XPS of the −NH 2 -functionalized Gly@UiO-66 framework before Hg(II) shows two peaks. The first is centered at 399.49 eV and assigned to the neutral form of amine −NH 2 , and the second peak at 401.37 eV is assigned to the protonated amine sites (−NH 3 + ) (Figure a). It is clear that the majority ratio (71%) of amine sites of the as-synthesized Gly@UiO-66 framework are protonated. Also, a full-range XPS survey of as-synthesized Gly@UiO-66 confirms the presence of chloride ions (Figure S14).…”
Section: Resultsmentioning
confidence: 98%
“…The N(1s)-core XPS of the −NH 2 -functionalized Gly@UiO-66 framework before Hg(II) shows two peaks. The first is centered at 399.49 eV and assigned to the neutral form of amine −NH 2 , and the second peak at 401.37 eV is assigned to the protonated amine sites (−NH 3 + ) (Figure a). It is clear that the majority ratio (71%) of amine sites of the as-synthesized Gly@UiO-66 framework are protonated. Also, a full-range XPS survey of as-synthesized Gly@UiO-66 confirms the presence of chloride ions (Figure S14).…”
Section: Resultsmentioning
confidence: 98%
“…The results of XPS show that there are two peaks at different binding energies for the as-synthesized sample of Gly@UiO-66 (Figure a). The peak at 399.49 eV is related to the free -NH 2 sites, while the second peak at 401.37 eV originates from the presence of protonated amine (-NH 3 + ) sites. According to the area under each peak, the amine groups of glycine are 29% in the free -NH 2 state and 71% in the -NH 3 + state while the XPS spectra of Gly@UiO-66 after the removal process display only one peak, 399.83 eV at pH 5 (Figure b) and 399.88 eV at pH 7 (Figure c). These peaks lie in the free -NH 2 region of energy. This observation shows that the protonated -NH 3 + sites are deprotonated during removal to be coordinated to As­(III) species just like free -NH 2 sites.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, more complex hybrid adsorbents have been synthesized using the co-precipitation method. Wan et al [ 91 ] reported the results of a humic acid/L-cysteine-codecorated magnetite that has complex properties, resulting from functional groups, ion exchange, and negatively charged surfaces. In another study, Amini et al [ 87 ] reported a novel composite, GO/Fe 3 O 4 /OPO 3 H 2 /PCN-222, that can extract U(VI) in 3 min, with a capacity of 416.7 mg/g.…”
Section: Conventional Synthesis Methods Of Magnetic Adsorbentsmentioning
confidence: 99%